2022
DOI: 10.1111/jmg.12685
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic erosion and deep subduction in Central Tibet: Evidence from the discovery of retrograde eclogites in the Amdo microcontinent

Abstract: The Amdo microcontinent which separates the Qiangtang terrane to the north and the Lhasa terrane to the south is a key terrane for reconstructing the tectonic evolution of Central Tibet. We report the new finding of retrograde eclogites within the Amdo microcontinent in this study. The eclogites are characterized by peak metamorphic mineral assemblages of garnet, omphacite, rutile and quartz and underwent a four‐stage metamorphic evolution, including a peak eclogite facies stage (M1) at ~20–24 kbar and 580–620… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Von Huene & Scholl, 1991;Barth & Schneiderman, 1996;Clift & Vannucchi, 2004;Clift & Hartley, 2007;Pastor-Galán et al 2021) and rarely documented in continental subduction zones (e.g. Yin et al 2007;Lu et al 2018) or in back-arc basins (Peng et al 2022). Peng et al (2022) reported the occurrence of retrograde eclogites, characterized by peak metamorphic mineral assemblages with garnet, omphacite, rutile and quartz, within the Amdo microcontinent in central Tibet.…”
Section: B Timing and Tectonic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Von Huene & Scholl, 1991;Barth & Schneiderman, 1996;Clift & Vannucchi, 2004;Clift & Hartley, 2007;Pastor-Galán et al 2021) and rarely documented in continental subduction zones (e.g. Yin et al 2007;Lu et al 2018) or in back-arc basins (Peng et al 2022). Peng et al (2022) reported the occurrence of retrograde eclogites, characterized by peak metamorphic mineral assemblages with garnet, omphacite, rutile and quartz, within the Amdo microcontinent in central Tibet.…”
Section: B Timing and Tectonic Implicationsmentioning
confidence: 99%
“…Yin et al 2007;Lu et al 2018) or in back-arc basins (Peng et al 2022). Peng et al (2022) reported the occurrence of retrograde eclogites, characterized by peak metamorphic mineral assemblages with garnet, omphacite, rutile and quartz, within the Amdo microcontinent in central Tibet. These authors suggest that tectonic erosion associated with the subduction of the Amdo microcontinent beneath the Tethys Ocean accounts for the deep subduction induced by tectonic erosion of the overriding plate.…”
Section: B Timing and Tectonic Implicationsmentioning
confidence: 99%
“…1A). This suture zone is mainly composed of Mesozoic flysch deposits, mélanges, high‐grade metamorphic rocks, scattered ophiolitic domains and intraplate ocean island domains (Shi et al ., 2012; Zhang et al ., 2017; Li et al ., 2019; Tang et al ., 2021; Fan et al ., 2021b; Hu et al ., 2022; Liu et al ., 2022; Peng et al ., 2022).…”
Section: Geological Backgroundmentioning
confidence: 99%